Peripheral vascular changes in the lower limbs following cocaine abuse. Issue 3 (2nd April 2020) - Camilleri, N.; Mizzi, A.; Gatt, A.; Papanas, N.; Formosa, C.
Abstract: Background: Worldwide, substance use disorder is on the rise, especially amongst the young generation. Although cocaine-induced cardiovascular and cerebrovascular events are well documented, knowledge about the relationship of cocaine use and its effect on arterial perfusion in the lower limbs is scarce. Objective: This study sought to investigate the relationship between cocaine use and peripheral arterial disease. Methods: The study population comprised 30 subjects' dependent on cocaine, smoking and alcohol [Group A] and another 30 subjects dependent on smoking and alcohol only [Group B]. A comprehensive lower limb vascular assessment was conducted utilizing pulse palpation, Doppler spectral waveform analysis, Ankle brachial pressure index (ABPI) and Toe brachial pressure index (TBPI) to determine the arterial perfusion status in the lower limbs. Results: Group A had lower ABPIs and TBPIs than Group B suggesting poorer vascular perfusion in lower limbs. Furthermore, a larger percentage of Group A had monophasic/continuous waveforms of all three pedal pulses compared to Group B. Conversely there was a higher percentage in Group B with biphasic/triphasic waveforms compared to Group A implying better vascular perfusion. Conclusion: In this study, cocaine use was associated with diminished arterial perfusion of the lower limbs suggesting that cocaine use has the potential to increase the risk of peripheral arterial disease. Regular vascular foot screening is warranted if foot complications are to be avoided.